ANALISIS PENGARUH LDR, CAR, BIAYA OPERASIONAL, NPL DAN ROA TERHADAP INTEREST SPREAD RATE (Studi Bank Umum Konvesional di Indonesia yang Terdaftar di BEI Periode 2011-2015) - Rahmania, Neza Fitri; Idris, Idris (Diponegoro Journal of Management, 2016)
Interest spread was difference between interest rate of time deposit with interest rate of credit obtained by banking. The purpose of this study is to investigate and assess whether affect determine the factors of interest spread at commercial banks Conventional listed on the Stock Exchange the period 2011 – 2015. Interest spread rate as a measure of the efficiency and profitability of the bank.Research sample used about 17 banks there are State Bank, Private National Bank, and Regional Bank. The method used is multiple regression analysis using normalitas test, multicollinearity, heteroscedasticity, autocorrelation, coefficient of determination, significant simultaneous and partial test. This study used purposive sampling method.The results of this study analysis that loans to deposit ratio, operating cost and return on asset significantly influence interest spread rate. Determination coefficient (adjusted R square) was about 0.218. or 21.8 percent. Whereas the remainder about 78.2 percent influenced by other factors out of research model.